Advanced zinc-polymer composites for marine corrosion protection and self-healing - Sharma, Sanjay; Girish, Santhosh; Nayaka, G. P.; Shiva Samhitha, S.; Pilliadugula, Rekha; Shivamurthy, B. P.; Gurumurthy, S. C.; Ruiz-Robles, Mitchel A.; Rojas, D.; Surabhi, Srivathsava (NPJ Materials Degradation, 2025)
Steel corrosion in saltwater costs over \$2.5 trillion annually. This review highlights advancements in zinc and polymer-based coatings for marine protection. It covers traditional methods and emerging technologies like nanoparticle-enhanced alloys, conducting polymers, metal organic frameworks (MOFs), and 2D materials. These offer improved resistance, self-healing, and intelligent protection with a future focus on sustainability and extended service life for marine infrastructure.